2016
DOI: 10.2109/jcersj2.16072
|View full text |Cite
|
Sign up to set email alerts
|

Processing and characterization of polymer derived SiOC foam with hierarchical porosity by HF etching

Abstract: A simple process for synthesizing SiOC foams with low density (45115 kg/m 3 ) and high porosity (9598%) is reported here. The process involves the impregnation of a flexible polyurethane foam with a preceramic polymer solution and pyrolysis in the inert atmosphere. SEM analysis showed that the resultant SiOC foam had a fully open interconnected porous structure with dense struts. N 2 adsorption test performed on the as-pyrolyzed SiOC foams showed very low surface area, which can be increased by leaching out th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 25 publications
0
17
1
2
Order By: Relevance
“…Figure b). Compressive strength was found to increase with increase in the pyrolysis temperature unlike the results of similar samples by Soraru et al (cf Table ). The MX3P samples showed higher strength as compared to the MX2P samples, indicating profound influence of densified struts on mechanical properties of reticulated ceramics.…”
Section: Resultscontrasting
confidence: 72%
See 2 more Smart Citations
“…Figure b). Compressive strength was found to increase with increase in the pyrolysis temperature unlike the results of similar samples by Soraru et al (cf Table ). The MX3P samples showed higher strength as compared to the MX2P samples, indicating profound influence of densified struts on mechanical properties of reticulated ceramics.…”
Section: Resultscontrasting
confidence: 72%
“…The effect of various process parameters in the fabrication of the porous ceramic bodies have been studied in the literature . The creation of higher surface area in the cellular SiOC ceramics by reactive etching of the SiO 2 domains has been demonstrated . Nevertheless, the effect of crosslinking temperature in the case of preceramic polymer derived porous bodies has not been explored in previous studies, which becomes the cornerstone of the current work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The closest research work to this approach was proposed by Szczurek et al when they showed the possibility of processing carbon periodic cellular architectures by coating, using hydrothermal conditions, a 3D printed polymeric lattice with a resorcinol‐formaldehyde resin followed by high‐temperature pyrolysis. On the other hand, the PDC process was used to replicate polyurethane foams and, accordingly, different reticulated ceramic foams in the general Si–C–O system have been obtained . This method has been shown to be simple and cost effective, and allows for the control of the density of the final ceramic foam by varying the polymer/PU foam mass ratio used in the impregnation step.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the PDC process was used to replicate polyurethane foams and, accordingly, different reticulated ceramic foams in the general Si-C-O system have been obtained. [16][17][18][19] This method has been shown to be simple and cost effective, and allows for the control of the density of the final ceramic foam by varying the polymer/PU foam mass ratio used in the impregnation step. In this study, we will show that polymer-derived SiCN ceramic lattices can be easily processed by replicating 3D printed cubic and tetrakaidecahedron polymeric periodic cellular architectures.…”
Section: Introductionmentioning
confidence: 99%